Bilingualism in Childhood and its Effect on Children’s Academic Performance - Alvim, Marta (Trinity College (Dublin, Ireland). School of Education, 2022)
The present thesis aims to explore how the acquisition and knowledge of more than one language impacts the development of social and academic skills in young learners, and what influence this multi-linguistic perception can bring upon children growing up within an environment where the the family and cultural context differentiate in language. Furthermore, it also focuses on the qualitative performance of school-aged children and explores the influences multi and mono-lingual parents, the society they’re introduced in and the educational system may have on their cognitive skills, while their minds and bodies are still growing and evolving. Following a desk-based research process, this dissertation’s empirical material comprises student-teacher-parent studies, papers on linguistic-acquirement skills in children and preadolescents and other editorial pieces on bilingualism in young learners and its relation with school performance. Theoretical frames of reference are based on four dimensions of learning, regardless of how many languages a child masters: content, social, educational and emotional, which, consequently, all have influence on their productivity within an academic scenario. The results reveal that the exposure to a bilingual family context and/or school context had the potential to improve a child’s social relations and increase participation, collaboration and on-task communication with peers and even strangers, due to the understanding of more than one linguistic concept. However, if not done correctly and with the support and constant participation of adult guardians to ensure the correct development of both languages, growing up in a multilingual environment has been seen to cause poor lexical awareness, grammatical confusion and even a lack of sense of belonging in social circumstances. Three literary review studies compared both perspectives of whether a bilingual child’s school performance is directly influenced by their linguistic capacity or not. Results revealed slightly different realities that seem to vary according to individuality instead of the bilingual population niche as a whole. An overarching conclusion is that the capacity of an individual to acquire multi-lingual skills easily and naturally is more strongly related to their excellent academic performance, rather than an individual that possesses two mother tongues from birth, which for them, is considered just a normal core-skill to have and is therefore not related to their scholastic capacities. Children that naturally show a bigger dexterity for languages seem to appeal to cognitive, social and emotional dimensions of learning more effortlessly and have a higher potential to broaden and achieving theoretical and physical approaches in education growing up.
Keywords: Psychology of Education); Education